The great cheese robbery - Warnes, Tim (London : Little Tiger Press, 2015)
Daddy Elephant is as big and strong as a tractor. But he's terrified of mice! So when a mouse tries to steal the elephants' cheese, Daddy is too scared to stop him! Can little Patrick Elephant save the cheese - and his father?
Keywords: Children's stories